THE ROLE AND ECONOMIC IMPORTANCE OF TOURISM IN MODERN SOCIETY - Berdiqulova Mahbuba Erkinjon qizi; Rahmonnazarova Saodat Egamnazar qizi (TADQIQOTLAR, 2026)
ABSTRACT This article analyzes the role and economic importance of tourism in modern society. Tourism is one of the key sectors of the national economy, contributing to gross domestic product growth, employment, and regional infrastructure development. It also strengthens cultural exchange and socio-economic cooperation between countries. The paper examines trends in domestic and international tourism, service quality, and the importance of sustainable tourism principles. The study concludes that tourism is one of the significant drivers of economic growth.